Evaluasi Kinerja Sistem Drainase Berdasarkan Debit Limpasan Dan Kapasitas Saluran Di Medan Tembung - Rachel Yunita Silitonga; Rendi Siahaan; Yuni Yolanda (CV. SINAR HOWUHOWU, 2026)
Sedimentation in drainage channels is one of the main factors that can reduce flow capacity and hydraulic performance. This study aims to analyze the effect of sedimentation levels on flow discharge in several drainage channel segments with different cross-sectional shapes, namely rectangular and trapezoidal, as well as varying channel dimensions. The data used include channel width, channel height, sediment thickness, and water surface elevation in each segment. Flow discharge is calculated using the Manning equation to determine the actual flow conditions. The results show that higher sedimentation levels significantly reduce flow discharge, particularly in segments with smaller channel dimensions. In addition, rectangular cross-sections with larger dimensions tend to provide better flow capacity compared to smaller trapezoidal sections. Therefore, sedimentation plays an important role in influencing the performance of drainage systems.